2017
DOI: 10.1159/000477550
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Obstruction of Uncommon Cause and Point-of-Care Ultrasonography - Where Do We Stand

Abstract: Malignant neoplasms of the small bowel, especially from the jejunum, are among the rarest types of cancer. Given its location, a delayed diagnosis is frequent and sometimes only made in an emergency context. The authors present a case of intestinal obstruction, where ultrasonography was pivotal in establishing a diagnosis. Point-of-care ultrasonography seems to be particularly sensitive in assessing emergency patients with abdominal pain, allowing effective orientation and saving human and technical resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Intestinal obstruction is a clinical multiple acute abdomen disease with a mortality rate of about 5%-10%. Previous studies have shown that intestinal obstruction can not only cause physical harm but also lead to psychological problems such as depression and anxiety [ 11 , 12 ]. Furthermore, those who lack correct recognition of intestinal obstruction lack confidence in the treatment of the disease, and the above psychological problems are more prominent [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal obstruction is a clinical multiple acute abdomen disease with a mortality rate of about 5%-10%. Previous studies have shown that intestinal obstruction can not only cause physical harm but also lead to psychological problems such as depression and anxiety [ 11 , 12 ]. Furthermore, those who lack correct recognition of intestinal obstruction lack confidence in the treatment of the disease, and the above psychological problems are more prominent [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%